Economically Important Fruit Flies (Diptera: Tephritidae) in Ghana and Their Regulatory Pest Management - Elvis Opoku; Muhammad Haseeb; Erick J. Rodriguez; Gary J. Steck; Maria J. S. Cabral (Insects)
Tephritid fruit flies are serious pests of Ghana’s numerous economically important fruits and vegetables. Their damages include rotting, premature ripening, and dropping of fruits, which lead to severe production losses, reduction in export volumes, trade restrictions, and other health implications when infested fruits are consumed. Due to the activities of these pests, less than 10% of fruits (especially mango) and vegetables produced are exported, and more than 60% of them end up in waste yearly. With current regulatory measures, Ghana has made significant progress in managing fruit flies, especially after the European Union (EU) ban in 2015. However, the pests remain problematic in the sub-region. A more coordinated nationwide approach and investments in postharvest treatment facilities are anticipated to help reduce pest populations, increase trading volumes and incomes, increase access to other markets, including the United States, and boost Ghana’s economy. It is estimated that for every US$1 invested in managing fruit flies, the return on investment is US$93.